2013
DOI: 10.1186/2052-3211-6-9
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescribing in women during and after delivery in a non-teaching, tertiary care hospital in Ujjain, India: a prospective cross-sectional study

Abstract: ObjectivesAntibacterial drugs (hereafter referred to as antibiotics) are crucial to treat infections during delivery and postpartum period to reduce maternal mortality. Institutional deliveries have the potential to save lives of many women but extensive use of antibiotics, add to the development and spread of antibiotic resistance. The aim of this study was to present antibiotic prescribing among inpatients during and after delivery in a non-teaching, tertiary care hospital in the city of Ujjain, Madhya Prade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 26 publications
1
27
2
Order By: Relevance
“…Use of antibiotic prophylaxis is widely recommended after caesarean section because there is a clear systematic review that it reduces incidence of 11 Third generation cephalosporin were also observed to be commonly used in other studies also. 10,12 This group of drugs are highly potent and have wide spectrum, active against both gram positive and gram negative organisms and in present study maximum of the antibiotics after surgical intervention was cephalosporin.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Use of antibiotic prophylaxis is widely recommended after caesarean section because there is a clear systematic review that it reduces incidence of 11 Third generation cephalosporin were also observed to be commonly used in other studies also. 10,12 This group of drugs are highly potent and have wide spectrum, active against both gram positive and gram negative organisms and in present study maximum of the antibiotics after surgical intervention was cephalosporin.…”
Section: Discussionmentioning
confidence: 54%
“…In our study, maximum number of patients were in age group of less than 30 years and were admitted as full term pregnancy with normal delivery and these patients were prescribed with oral antibiotic cefuroxime (17.3%) and amoxycillin clavulanate (6.59%) for 7 to 10 days and it is in concurrence with other studies. 10 The antibiotic prescribed after caesarean section in our study was ceftriaxone in combination with tinidazole and gentamycin. Use of antibiotic prophylaxis is widely recommended after caesarean section because there is a clear systematic review that it reduces incidence of 11 Third generation cephalosporin were also observed to be commonly used in other studies also.…”
Section: Discussionmentioning
confidence: 90%
“…We have earlier reported high proportion of antibiotic use for common infections among outpatients [ 24 ] and among admitted patients with a suspected focus of infections [ 25 , 26 ]. High rate of antibiotic prescribing has been noted in surgical ward [ 25 , 27 ], in peri-partum period [ 28 ] and in patients admitted in medical intensive care unit [ 29 ]. Inappropriate choice of antibiotics and also inappropriately long duration of antibiotic therapy for post-surgery prophylaxis has been documented [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic prescription to this group of patients cannot be justified as even the prophylactic use of antibiotics for FTND is not recommended (39). A previous study from Ujjain district in India has shown an antibiotic prescribing to 87% FTND patients (40).An episiotomy is a possible indication for antibiotic prophylaxis in FTND; however, according to a Cochrane review, further studies are required to ascertain the need for antibiotic prophylaxis for an episiotomy (41). Thus, a targeted study is suggested to investigate the rationality of prescribing antibiotics for FTND.…”
Section: Antibiotic Prescribing In the Groupsmentioning
confidence: 99%